2005
DOI: 10.1158/0008-5472.can-04-2820
|View full text |Cite
|
Sign up to set email alerts
|

Human Carcinoma Cell Growth and Invasiveness Is Impaired by the Propeptide of the Ubiquitous Proprotein Convertase Furin

Abstract: Furin, a potent proprotein convertase involved in activation of several cancer-related substrates, is synthesized as an inactive zymogen, thus minimizing the occurrence of premature enzymatic activity that would lead to inappropriate protein activation or degradation. This natural inhibitory mechanism is based on the presence of an inactivating prosegment at the NH 2 terminal of the zymogen. After initial autocatalytic cleavage, the prosegment remains tightly associated with the convertase until it reaches the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 40 publications
2
35
0
Order By: Relevance
“…In contrast, overexpression of ppFurin has thus far consistently resulted in reduced malignant phenotypes of various cancer cells (ref. 18, and the present study). Taken together, our results strongly suggest that regulation of the MMP-9/TIMP-1 ratio by PCs in breast cancer cells may be one of the major factors that control their invasive and metastatic abilities.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…In contrast, overexpression of ppFurin has thus far consistently resulted in reduced malignant phenotypes of various cancer cells (ref. 18, and the present study). Taken together, our results strongly suggest that regulation of the MMP-9/TIMP-1 ratio by PCs in breast cancer cells may be one of the major factors that control their invasive and metastatic abilities.…”
Section: Discussionsupporting
confidence: 76%
“…Accordingly, overexpression of Furin has been established in various types of cancers (2,10,14) and has been linked to aggressive behavior in some model systems (14). Using ppFurin cells, Lopez de Cicco et al showed that overexpression of this inhibitor in various head and neck squamous cells induced significant reductions in cell proliferation, tumorigenicity, and invasiveness (18). These changes were directly related to the inhibition of Furin-mediated activation of crucial cancer-related substrates (18).…”
Section: Discussionmentioning
confidence: 99%
“…The present study demonstrates the importance of PCs in early and late liver colonization by metastatic colon cancer cells and suggests the potential use of PC inhibitors as new therapeutic agents for liver colorectal metastasis prevention. In certain situations specific inhibition of a single PC may be sufficient and more appropriate, as previously reported for furin, the specific inhibition of which was revealed to abolish the malignant phenotype of various malignancies (55). Evidently, more understanding of the molecular mechanisms of the PC inhibitors by using various in vitro and in vivo models is required before testing their efficacy in human cancers.…”
Section: Figurementioning
confidence: 87%
“…Furin activation plays a vital role in tumor process (Lopez de Cicco et al, 2005). Furin inhibitor α1-PDX has been used to block Furin activity and to prevent cancer metastasis in biochemical, cellular and animal studies (Molloy and Thomas, 2001).…”
Section: Introductionmentioning
confidence: 99%